Efektivitas Model NHT Berbantuan GeoGebra terhadap Motivasi Belajar dan Pemecahan Masalah Siswa SMA - Irgi Al-Farizi; Sutarto Sutarto; Yuntawati Yuntawati (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aimed to examine the effectiveness of the Numbered Heads Together (NHT) cooperative learning model assisted by GeoGebra on students’ learning motivation and mathematical problem-solving ability simultaneously. A quantitative approach with a quasi-experimental method was employed using a pretest–posttest non-equivalent control group design. The sample consisted of an experimental class taught using GeoGebra-assisted NHT and a control class taught using conventional learning. Data were collected through a mathematical problem-solving test and a learning motivation questionnaire, then analyzed using an independent t-test, N-Gain, and MANOVA. The independent t-test results showed no significant difference in students’ learning motivation between the experimental and control classes, while a significant difference was found in mathematical problem-solving ability. The N-Gain results indicated that problem-solving ability increased by 63% in the experimental class and 48% in the control class, showing a 15% advantage for the experimental class. However, learning motivation decreased by 0.1% in the experimental class and increased by 9% in the control class, both categorized as ineffective. The MANOVA results revealed a significant simultaneous difference between the two classes. Therefore, GeoGebra-assisted NHT was more effective in improving mathematical problem-solving ability but was not effective in enhancing students’ learning motivation.